New insights into the effect of gypsum on hydration and elasticity development of C3S paste during setting. (September 2022) - Huang, Tingjie; Yuan, Qiang; Zuo, Shenghao; Xie, Youjun; Shi, Caijun
Abstract: Gypsum has been known to regulate cement setting since more than 100 years, whereas the understanding of the physio-chemical mechanism remains incomplete. Here, we investigated the influence of gypsum on elasticity evolution of fresh tricalcium silicate (C3 S) paste through small amplitude oscillation shear method. Isothermal calorimetry, X-ray diffraction, 1 H nuclear magnetic resonance, and zeta potential measurements were performed to explore the corresponding changes in hydration, microstructure, and colloidal interaction. It was found that incorporating gypsum is beneficial for inter-particle agglomeration by significantly weakening electrostatic repulsion force between particles, which accelerates elasticity development in the early period of setting. Although the retardation effect of gypsum on C3 S hydration hinders the further development of elasticity in the later period, the more divergent needle-like calcium silicate hydrate (C-S-H) and the stronger cohesion of the C3 S particle network in presence of gypsum lead to a higher elasticity at the same hydration degree.